A color vision approach for reconstructing color images in different lighting conditions based on auto encoder technique using deep neural networks - Gomes, Paul Richie; Uddin, Muhammad Arman; Sabuj, Hasibul Hasan; Faiz, Raian Ibn (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.